From Multisensory Assessment to Functional Interpretation of Social Behavioral Phenotype in Transgenic Mouse Models for Autism Spectrum Disorders - Arakawa, Hiroyuki (Frontiers in Psychiatry, 2020)
Autism spectrum disorder (ASD) is a common heterogeneous disorder, defined solely by the core behavioral characteristics, including impaired social interaction and restricted and repeated behavior. Although an increasing number of studies have been performed extensively, the neurobiological mechanisms underlying the core symptoms of ASD remain largely unknown. Transgenic mouse models provide a useful tool for evaluating genetic and neuronal mechanisms underlying ASD pathology, which are prerequisites for validating behavioral phenotypes that mimic the core symptoms of human ASD. The purpose of this review is to propose a better strategy for analyzing and interpreting social investigatory behaviors in transgenic mouse models of ASD. Mice are nocturnal, and employ multimodal processing mechanisms for social communicative behaviors, including those that involve olfactory and tactile senses. Most behavioral paradigms that have been developed for measuring a particular ASD-like behavior in mouse models, such as social recognition, preference, and discrimination tests, are based on the evaluation of distance-based investigatory behavior in response to social stimuli. This investigatory behavior in mice is regulated by multimodal processing involving with two different motives: first, an olfactory-based novelty assessment, and second, tactile-based social contact, in a temporally sequential manner. Accurate interpretation of investigatory behavior exhibited by test mice can be achieved by functional analysis of these multimodal, sequential behaviors, which will lead to a better understanding of the specific features of social deficits associated with ASD in transgenic mouse models, at high temporal and spatial resolutions.